The AMPK-like protein kinases Sik2 and Sik3 interact with Hipk and induce synergistic tumorigenesis in a Drosophila cancer model - Yu, Kewei; Ramkumar, Niveditha; Wong, Kenneth Kin Lam; Tettweiler, Gritta; Verheyen, Esther M. (Frontiers in Cell and Developmental Biology, 2023)
Cancer is the second leading cause of death in the world. According to the International Agency for Research on Cancer, 20.4% of the population will be diagnosed with cancer in their lifetime. The development of human cancer is a complex and multistep process, which involves changes in proteins that play vital roles in all the cells, tissues, and organs in our bodies. In particular, changes in the overall amount of protein and interactions with other proteins can cause cancer. We use the fruit fly as an animal model to study how interactions between Salt-inducible kinases (Siks) and Homeodomain-interacting protein kinases (Hipk) can cause tumour growth. Both proteins are highly conserved through evolution. We established that when both proteins are expressed at high levels, they caused significant tumour growth in the fruit fly larval tissue. Reducing Sik protein levels reduced the ability of Hipk to induce tumorigenesis, suggesting that Siks can govern the function of Hipk. This work will help us to understand in more detail how tumors overexpressing Siks and Hipk develop. We anticipate that this will enable new or improved treatments that target tumorigenesis more effectively.